Relationship between sediment type, total organic matter, and water quality on mangrove density on Tunda Island, Serang Banten - Pratama, Fadila Aditia Putri; MS, Yuniarti; Zallesa, Sheila; Sunarto, Sunarto (Universitas Malikussaleh, 2023)
Environmental conditions that are quite important in the growth of mangroves are the type of sediment, organic matter, and water quality because the organic matter produced can be useful for mangrove fertility. This study aims to determine the type of sediment, the percentage of total organic matter, water quality, mangrove density, and determine the relationship between sediment types, total organic matter, and water quality on mangrove density on Tunda Island, Serang, Banten. This study used a survey method while collecting data using a purposive sampling method. Mangrove density was obtained through the line transect plot method. The sediment type test used the dry sieving method, the total organic matter (BOT) test used the loss on ignition (LOI) method, the statistical test used the multiple correlation method. All data was then analyzed in a quantitative descriptive manner. The results of the study are that the type of sediment in Tunda Island mangroves is dominated by silty sand and sand. The total organic matter contained in mangrove sediments ranges from 2.40% - 3.62% which is included in the moderate to high category. Salinity values ranged from 31 - 34.33 ppt included in the high category. The pH value ranges from 7.33 - 7.70 which is included in the good category for mangrove growth. Temperature values ranging from 27.37oC - 31.63oC are included in the good category for mangrove growth because they can still grow and develop normally. The mangrove density level is dominated by the dense category, which is 2,400 ind/Ha at station 1 and 1,700 ind/Ha at station 2, and the rare category is 1,000 ind/Ha at station 3 and 900 ind/Ha at station 4. There is a significant relationship between sediment type, total organic matter, water quality with mangrove density.Keywords: BOT; Mangroves; Sediment; Water Quality